Set up of a secondary on-board charger fed by PV DC station with grid injection for fast charging the recent city cars - Arrach, Mohamed; Tahiri, Fatima Ezzahra; Lokriti, Abdesslam; Chikh, Khalid (International Journal of Power Electronics and Drive Systems (IJPEDS), 2025)
In this article, we propose a secondary high-power charger provided by a photovoltaic source with grid connection. The high-power charger is composed of a phase shift full bridge (PSFB) DC-DC converter controlled by a constant voltage constant current algorithm based on PI control. The first stage is composed of a PV panel source, controlled by a fuzzy logic using a maximum power point tracking (MPPT) algorithm, associated with a synchronous boost converter to set up the voltage at the standard common 400 V bus level. While the charger is a second stage composed of a phase shift converter for step down and adapting the voltage and the charging current for the battery of the urban electric car. We have also proposed the grid connection with a simple optimization to inject the generated power into the electrical grid when no car is connected to the power station. To achieve this goal, simulation results of the proposed configuration control techniques by using the MATLAB/Simulink environment are presented and discussed at the end of this paper.